Problematik Data Pemilih pada Pemilihan Kepala Daerah Tahun 2018 Di Kota Medan - Muhammad Husni Thamrin; Muhammad Arifin Nasution; Faiz Albar Nasution (Sospol : Jurnal Sosial Politik, 2020)
Updating voter data is one of the most important indicators of the success of the Pilkada in Indonesia. However, the accuracy of voter data in the city of Medan is still a problem that affects the level of public participation in the Pilkada. This phenomenon, has an impact on the constitutional rights of the people, determines the number of polling stations, the availability of ballots and budget formulation. This study aims to analyze voter data problems and the role of the Medan KPU in updating voter data. Edwards' theory about policy implementation is used as an analytical tool for public participation in the 2018 Pilkada in Medan City. This research uses descriptive qualitative method. Data collection techniques through documentation and in-depth interviews. Data analysis using Miles and Huberman's techniques, among others: data reduction, data display and drawing conclusions. The problem of 2018 Pilkada in Medan was influenced by multi factors, including the accuracy of the DPT, the HR of Voter Data Updating Officers and regulations which tended to be consistent regardless of other factors, such as the removal of a very large number of DPT. Therefore, it requires mutual attention, synergy, and commitment to all related parties to carry out their duties and functions in Pilkada activities. The urgency of the Pilkada as a means of community sovereignty must be protected collectively in terms of quantity and quality.